Association between political group participation and depressive symptoms among older adults: an 11-year longitudinal study in Taiwan. (8th September 2021) - Lin, Yu-Chun; Yan, Huang-Ting
Abstract: Background: Given the speculation that political participation is causing an epidemic of depression, this study examined how participation in political and non-political groups influenced depressive symptoms among older adults in Taiwan. Methods: The 11-year follow-up data from the Taiwan Longitudinal Study on Ageing, covering 5334 persons aged 50 years and older, were analysed using random-effects panel logit models. Results: Engagement in social groups reduced the likelihood of depression (adjusted odds ratio [AOR]: 0.71, 95% confidence interval [CI]: 0.64–0.80). However, there was a greater likelihood of depressive symptoms among older adults who were engaged in political groups when compared with those who were engaged in non-political groups (AOR: 1.87, 95% CI: 1.31–2.65). For older adults who remained politically engaged, participation in a greater number of non-political group types was associated with a lower likelihood of depression (e.g. at 1: AOR: 0.53, 95% CI: 0.30–0.91; at 2+: AOR: 0.35, 95% CI: 0.18–0.67); this numbers-based effect was not prevalent among those who were solely engaged in non-political groups. Conclusions: Political group attendance can result in negative mental health outcomes among older adults. Our findings suggest that reducing the prevalence of depression through social participation is conditional to the engagement type.